Functional diversity enhances grassland productivity, but species identity drives performance - Supriya Verma; Antje Herrmann; Friedhelm Taube; John Kormla Nyameasem; Daniel Ehrhard; Carsten S. Malisch; Christof Kluß; Arne Poyda (Agriculture, Ecosystems & Environment, 2026)

Adult survival has a stronger role than productivity in the annual population change of European songbirds - Inari Nousiainen; Laura Bosco; Petteri Lehikoinen; Rob Robinson; Juan Arizaga; Jaroslav Cepák; Wolfgang Fiedler; Olaf Geiter; Ian Henshaw; Christof Herrmann; Marc Illa; Henk P. van der Jeugd; et al. (Oecologia, 2025)
Biodiversity is decreasing at an alarming rate, and there is an urgent need to understand the demographic drivers behind population declines. Therefore, it is important to study the different stages of a species’ life cycle, including adult survival and productivity. It is still poorly understood whether adult survival or productivity has a stronger role in population change, and how the role of adult survival and productivity varies spatially in relation to species’ traits. We used bird ringing data from the European Constant Effort Sites (EuroCES) project from the years 2000 to 2021, with 1.2 million captures of 33 songbird species from ten European countries. We investigated the role of productivity and adult survival in annual population change and how it was affected by spatio-climatic gradient (measured as average breeding season temperature per country), migratory strategy (long- vs. short-distance and sedentary birds), and breeding habitat (forest vs. reeds) using linear mixed effect models. Overall, our results show that adult survival is a more important driver of annual population change than productivity within European songbirds. The importance of adult survival and productivity varied spatially, both having a weaker influence in warmer regions. Furthermore, the role of adult survival was stronger for long-distance migrants compared to short-distance migrants. Acknowledging that adult survival has a stronger role in annual population change than productivity can help design more robust conservation actions, especially regarding long-distance migratory songbirds.

Phenological Plasticity and Its Temperature‐Related Drivers in Common Songbirds Across Europe - Paul Cuchot; Timothée Bonnet; Robert A. Robinson; Juan Arizaga; Wolfgang Fiedler; Olaf Geiter; Ian Henshaw; Christof Herrmann; Henk van der Jeugd; Zsolt Karcza; Arantza Leal; Petteri Lehikoinen; et al. (Global Change Biology, 2025)
Phenological plasticity—the ability of organisms to adjust the timing of life‐history events in response to environmental variability—is the primary adaptive mechanism for many organisms to changing seasonality (e.g., earlier spring). By enabling alignment between life‐history events and resource availability, it helps to maintain fitness despite changing environmental conditions. Theory predicts that phenological plasticity should vary among populations because of heterogeneity in environmental variability, and among species because of differences in life‐history (e.g., migration distance) and phylogenetic constraints. However, comprehensive, multi‐species, and cross‐population analyses of phenological plasticity remain scarce. Here, we address this gap by using a unique, four‐decade dataset from Europe‐wide monitoring of common songbirds. Our approach reveals how variation in phenological plasticity is structured according to site temperature properties, both within and across species. We found that long‐distance migrants generally exhibit lower plasticity than residents or short‐distance migrants, highlighting a fundamental constraint tied to migration strategy. Within species, populations inhabiting sites with predictable temperature profiles showed slightly stronger plastic responses, particularly among single‐brooded species and those adapted to warmer breeding conditions. Notably, populations from the fastest‐warming regions demonstrated marginally greater plasticity, regardless of other ecological traits, suggesting a global tendency for increased responsiveness in rapidly changing climates. These findings confirm and extend patterns previously observed at smaller scales, offering a more nuanced understanding of how local temperature conditions drive phenological plasticity. By demonstrating that the interplay between local environmental conditions and life‐history traits underpins variation in breeding phenological responses, our study refines the current framework for predicting adaptive potential across populations and species under climate change.

Temporal Changes to Migratory Fuel Load in Migratory Birds Across Europe - Jennifer Anne Border; Robert A. Robinson; James W. Pearce‐Higgins; Chris M. Hewson; Christine Howard; Philip A. Stephens; Stephen G. Willis; Jan A. C. von Rönn; Pierre‐Yves Henry; Romain Lorrilliere; Lorenzo Serra; Simona Imperio; et al. (Global Change Biology, 2025)
Climate change is a major threat to biodiversity, and migratory animals are particularly vulnerable, due partly to their reliance upon good resource availability across a network of sites at specific times. Migrants perform vital ecosystem functions, transferring significant resources across large spatial scales, but the impacts of climate change on the ability of individuals to complete these journeys are poorly studied. Collecting the large‐scale and long‐term data on the condition of individuals during migration to address this is challenging, but in migratory birds, we have a model system for which a large network of ringers (banders) collect individual data on body size and mass, enabling variation in body condition to be tracked. We used long‐term ringing data on 33 Afro–Palearctic migratory bird species at 286 sites across Europe to demonstrate a large‐scale decrease in migratory fuel loads during autumn over the last 40 years, but not in spring. Declines were strongest across southern Europe and linked to rising temperatures. The timing of autumn fuelling has also shifted, occurring earlier at northern sites and later at southern sites. These relationships varied depending on diet and breeding cycle length. Obligate insectivores were more constrained by temperature in the timing and magnitude of fuelling than frugivores. Species with short breeding cycles departed later at southern sites in warmer years, likely reflecting an extended breeding season. Altogether, these latitudinally varying findings suggest a trade‐off between maximising productivity or maximising adult survival as climate drives changing constraints on breeding season length and resource availability. Similar climate‐induced trade‐offs may be happening in other migratory taxa with the potential to influence population trends.

Sex- but not age-biased wind turbine collision mortality in the White-tailed Eagle Haliaeetus albicilla - Christian Heuck; Christof Herrmann; Juliane Wendt; Oliver Krone; Roland Brandl; Jörg Albrecht (Journal of Ornithology, 2020)

Effects of catch crops on silage maize (Zea mays L.): yield, nitrogen uptake efficiency and losses - Martin Komainda; Friedhelm Taube; Christof Kluß; Antje Herrmann (Nutrient Cycling in Agroecosystems, 2018)

Ecological Efficiency of Maize-Based Cropping Systems for Biogas Production - Nikolai Svoboda; Friedhelm Taube; Christof Kluß; Babette Wienforth; Klaus Sieling; Mario Hasler; Henning Kage; Susanne Ohl; Eberhard Hartung; Antje Herrmann (BioEnergy Research, 2015)

Differential effects of habitat isolation and landscape composition on wasps, bees, and their enemies - Christof Schüepp; John D. Herrmann; Felix Herzog; Martin H. Schmidt-Entling (Oecologia, 2011)